Training on capacity building for editors in managing OJS-based journals - Mufti, Nandang; Taufiq, Ahmad; Hidayat, Arif; Sunaryono, Sunaryono; Muhammad, Helmi; Subadra, ST Ulfawanti Intan (Universitas Muhammadiyah Magelang, 2025)
Scientific publication is one of the means of sharing knowledge in the field of education, including learning processes, learning media, and other educational research findings. One of the most commonly used open-source platforms is the Open Journal System (OJS). However, new editors often have very limited knowledge regarding the journal's business processes. This community service activity aims to develop and enhance the competencies of journal editors in managing OJS-based journals. The program was conducted in two stages: the implementation stage, which included training through lectures and discussions, followed by the evaluation stage. The evaluation results indicate that the provided materials and hands-on practice significantly helped improve editors' knowledge of OJS-based journal management. Furthermore, after this training, editors became more proficient in article selection and copyediting processes.